Desperdício de Alimentos e Políticas Públicas - BRUNA LAÍS OJEDA CRUZ (2021)
Food waste has been a priority on international agendas, due to its environmental, economic, and social impacts. The fight against food waste requires changes in operational, productive and consumption practices, transforming practices in the food supply chain. A big change is to turn food waste into something that can be used and that can be reintroduced into the value chain. Therefore, in order to move from a linear to a circular economy, it is essential that conditions exist that support and directly contribute to this transition, such as education and public policies. In this context, this research aims to collaborate with the debate on food waste by analyzing public policies related to the reduction of food waste in Brazil, supported by the concept of the circular economy seeking to achieve the goal established in SDG 12.2. Having as a central question: Is the concept of the circular economy useful for the regulation of public policy to combat food waste in Brazil? From a qualitative approach, the elements of document analysis and systematic review were used. From the results of the research, it was possible to identify 37 bills to combat food waste. It was noted that the main strategy for combating food waste presented by the bills, is the proposal to donate food suitable for human consumption, followed by civil and criminal liability of natural and legal persons who donate food. Food waste recently gained prominence on the political scene with the approval of bill No. 1194 of 2020 that was transformed into Ordinary Law No. 14016 of 2020, and it is evident that even with the approval of the law, there are still major obstacles to be overcome. overcome in the fight against food waste, for this reason it is recommended as proposals for improvements to law No. 14.016 of 2020, initiatives that help everyone to see the consequences of food waste to spread awareness in society; the adoption of the food recovery hierarchy in the food supply chain in Brazil; the reverse cycle logistics needs to be established; actions to extend product life; and incentives for the adoption of the circular economy through monetary rewards to establishments that donate food to institutions. It was found that the correct and sustainable implementation of waste, established according to the hierarchy of food recovery together with the circular economy approach can help in combating food waste.